Peningkatkan hasil belajar passing bawah bola voli dengan pembelajaran kooperatif - Sahabuddin Sahabuddin; Hikmad Hakim (Seminar Nasional LP2M UNM, 2019)
This study aims to determine the learning outcome passing forearm volleyball at SMK Negeri 7 Makassar through cooperative learning. This study uses action research as much as two cycles with the design planning, observation, action, and reflection. The target in this study were students of SMK Negeri 7 Makassar office administration class, as many as 24 students. Sources of data obtained through the initial test and final test passing forearm volleyball. Data analysis techniques used in this research is descriptive. The results showed the beginning of the test until the end of the test. Results of preliminary tests showed the lowest value is 33.3 and the highest value of 66.7. Then the final test results in cycle one is the lowest value of 50 and 83.3 and the highest value was 62.50%. Learning will be unchanged or increase in cycle two, with the lowest value and the highest 58.3 91.7, with a percentage of 83.33%, and meets the criteria of achievement in action research is 80%. Conclusions from this research is the method of group learning positive effect in improving student achievement, marked by increased completeness.